2017
DOI: 10.3390/brainsci7050050
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Brain Plasticity of Functional Connectivity Modulated by Cognitive Training in Mild Alzheimer’s Disease and Mild Cognitive Impairment

Abstract: Alzheimer’s disease (AD) alters the functional connectivity of the default mode network (DMN) but also the topological properties of the functional connectome. Cognitive training (CT) is a tool to slow down AD progression and is likely to impact on functional connectivity. In this pilot study, we aimed at investigating brain functional changes after a period of CT and active control (AC) in a group of 26 subjects with mild AD (mAD), 26 with amnestic mild cognitive impairment (aMCI), and a control group of 29 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 84 publications
4
33
0
Order By: Relevance
“…Taken together, the moderate summary effects observed after multicomponent and multidomain interventions would be consistent with activation of compensatory mechanisms described by the STAC-r model such that multifaceted cognitive interventions may recruit alternate networks as neurocomputational support to aid primary functional networks process load demands (Barban et al 2017 ; Ciarmiello et al 2015 ; Onur et al 2016 ). As such, strategies which target both primary functional networks as well as alternate pathways simultaneously may be the most efficacious form of intervention for individuals with MCI.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Taken together, the moderate summary effects observed after multicomponent and multidomain interventions would be consistent with activation of compensatory mechanisms described by the STAC-r model such that multifaceted cognitive interventions may recruit alternate networks as neurocomputational support to aid primary functional networks process load demands (Barban et al 2017 ; Ciarmiello et al 2015 ; Onur et al 2016 ). As such, strategies which target both primary functional networks as well as alternate pathways simultaneously may be the most efficacious form of intervention for individuals with MCI.…”
Section: Discussionsupporting
confidence: 53%
“…are aggressively being sought to mitigate or slow illness progression (Cai and Abrahamson 2016 ; Curlik and Shors 2013 ; Kivipelto et al 2013 ; Lehert et al 2015 ; Simons et al 2016 ; Smith et al 2010 ). This may be especially important as cognitive training in MCI has been associated with increased activation in the hippocampus (Hampstead et al 2012b ; Rosen et al 2011 ), right inferior parietal lobe (Belleville et al 2011 ), frontoparietal network (Hampstead et al 2011 ), occipito-temporal areas (Onur et al 2016 ), and implicated in other processes (Barban et al 2017 ; Ciarmiello et al 2015 ; Maffei et al 2017 ). As such, identifying the cognitive interventions effective in MCI may, in turn, aid in targeting the neural networks with greater specificity at prodromal stages to alter illness trajectory away from more serious cognitive decline (Kim and Kim 2014 ; Shatenstein and Bargerger-Gateau 2015 ; Sitzer et al 2006 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, compared to patients with SCD, DMN subnetworks in aMCI group showed obvious differences in right SFGMP and left MFGOP belonging to FG. In previous studies, aMCI group showed more widespread topological changes involving the frontal lobes (Barban et al, 2017), and aberrant connectivity was also found in patients with SCD between DMN and FG due to cognitive impairment (Xue et al, 2019). Besides, an increasing trend of values of amplitude of low-frequency fluctuation (ALFF) and fractional ALFF were detected in FG (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…Thus, we anticipate that MINM may explain the connection mechanism for the formation of the brain network organization in AD patients.topological properties for evaluating the characteristics of human brain networks [8][9][10][11][12]. Taking the form of a graph, people can learn the alterations of brain network properties in terms of network connectivity, transitivity, efficiency, degree distribution, modularity, and small-world-ness between normal controls (NC) and AD patients [13][14][15]. Particularly, graph theory also provides numerous methods of network modeling for simulating the evolution processes of real complex networks [16][17][18][19].…”
mentioning
confidence: 99%